Ko-Infeksi HIV-TB: Studi Cross Sectional - Intan Pertiwi; Cicilia Windiyaningsih; Adria Rusli; Farida Murtiani (Jurnal Kesehatan Komunitas, 2023)
WHO states that co-infection of the disease that is often experienced by HIV/AIDS patients is Tuberculosis and is the main cause of mortality for HIV/AIDS patients. This study aims to determine the determinants of HIV-TB infection. Analytical research using case-control study design. The research sample was medical record data of HIV-TB co-infected patients at RSPI Prof. Dr. Sulianti Saroso in 2011-2016. The sample size is 160 with a random sampling technique. Analysis of univariate, bivariate, and multivariate data. The results showed that the factors of access to health facilities, weight loss, comorbid with other OIs, CD4 values ​​6 months after ARV and COPD were associated with HIV-TB infection with HIV in patients and the determinant factor of HIV-TB infection was weight loss. The incidence of HIV-TB Co-Infection can be influenced by factors of the patient's clinical condition and environmental factors. To improve services at the HIV department and TB DOTS department it is necessary to measure body weight for the nutritional status of HIV/AIDS patients.